الاحتراق النفسي لدى مدرسي العلوم الإنسانية في المدارس الثانوية - السامرائي، قصي محمد لطيف; توفيق، مروان حكم (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2016)
ازداد الاهتمام بظاهرة الاحتراق النفسي في مهنة الخدمات ولا سيما التعليم، ويمكن تحيد هذه الظاهرة إجرائيا بأنها التغيرات السلبية في الاتجاهات والسلوك المتعلقة بالفرد بوصفها رد فعل لضغوط العمل، ومن مظاهرها المهمة على سبيل المثال فقدان الاهتمام بالعمل بطريقة روتينية، والنقص في الدافعية، ومقاومة التغيير، وفقدان الابتكارية وللتثبت من وجود ظاهرة الاحتراق النفسي بين مدرسي العلوم الإنسانية للمرحلة الثانوية صمم الباحث استبانة تحتوي على (28) فقرة تناولت مصادر الضغط في مهنة التدريس وهذه المصادر هي: ١-سلوك الطلاب. ٢-علاقة المدرسين بعضهم ببعض. ٣-علاقة المدرسين بالإدارة. ٤ - علاقة المدرس بالمهنة. 5-الصراعات الذاتية. ٦-الأعراض التربوية والنفسية للضغوط. وللإجابة عن تساؤلات البحث أجريت المقارنة على أساس الجنس والخبرة، التدريسية فكشفت الدراسة عن وجود فروق بين الذكور والإناث من التدريسيين في ظاهرة الاحتراق النفسي. ولأهمية هذا الموضوع فإنه يحتاج إلى تركيز وتسليط الضوء عليه من قبل الباحثين في الاختصاصات التربوية والنفسية.
Increased attention to the phenomenon of burnout in the profession and in particular services Education, and can deviate from this phenomenon procedurally as negative changes in attitudes and behavior related to the individual as a reaction to the pressures of work, and manifestations of the task, for example, loss of interest in work in a routine manner, and a lack of motivation, and resistance to change, and the loss of innovative and prove the existence of the phenomenon of burnout among teachers Humanities in the secondary stage is designed to identify the researcher contain (28) paragraph addressed the sources of stress in the teaching profession, and these sources are: 1-student behavior. 2 - teacher relationship to each other. 3 - teacher relationship management. 4 - relationship with the teacher profession. 5 - self conflicts. 6- psychological and motheds symptoms of stress. To answer questions about the search conducted on the basis of the comparison of sex and teaching experience revealing study of the existence of differences between male and female faculty in the phenomenon of burnout. And the importance of this issue, he needs to focus and highlight it by researchers in educational and psychological disciplines.
Keywords: الاحتراق النفسي -- الضغوط المهنية -- التعليم الثانوي -- أعضاء هيئة التدريس